Eksploitasi Alam dan Perusakan Lingkungan (Istinbath Hukum atas Ayat-Ayat Lingkungan) - Reflita Reflita (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2015)
Environmental damage, especially in the form of land degradation, water and air, which are the resources supporting human, animal and plant life are allegedly assumed as the result of poor understanding of religious texts, lack of knowledge about nature and the anthropocentric view which considers that the universe was created solely for mankind. Therefore, in order to solve these various environmental problems, a solution referring to the holy book of Quran is mandatory. Damaging the environment by exploitation its natural resources is clearly antithetical to the teachings of Islam as the blessing of God to the universe. The Quran declares that humans are the caliphs in the earth and they must maintain the balance of this great precision universe created by God. Likewise, all forms of destruction are forbidden in Islam and such acts are unlawful. The culprit are entitled to penalties and sanctions in accordance with the level of mistakes they do.